The right care, every time: improving adherence to evidence-based guidelines. Issue 1 (23rd May 2017) - Runnacles, Jane; Roueché, Alice; Lachman, Peter
Abstract : Guidelines are integral to reducing variation in paediatric care by ensuring that children receive the right care, every time. However, for reasons discussed in this paper, clinicians do not always follow evidence-based guidelines. Strategies to improve guideline usage tend to focus on dissemination and education. These approaches, however, do not address some of the more complex factors that influence whether a guideline is used in clinical practice. In this article, part of the Equipped Quality Improvement series, we outline the literature on barriers to guideline adherence and present practical solutions to address these barriers. Examples outlined include the use of care bundles, integrated care pathways and quality improvement collaboratives. A sophisticated information technology system can improve the use of evidence-based guidelines and provide organisations with valuable data for learning and improvement. Key to success is the support of an organisation that places reliability of service delivery as the way business is done. To do this requires leadership from clinicians in multidisciplinary teams and a system of continual improvement. By learning from successful approaches, we believe that all healthcare organisations can ensure the right care for each patient, every time.